2015
DOI: 10.1039/c4dt00926f
|View full text |Cite
|
Sign up to set email alerts
|

An in situ spectroscopic study of the local structure of oxyfluoride melts: NMR insights into the speciation in molten LiF–LaF3–Li2O systems

Abstract: The local structure of molten LaF3-LiF-Li2O has been investigated by high temperature NMR spectroscopy. The (139)La and (19)F chemical shifts have been measured as a function of temperature and composition. The NMR spectra show that Li2O reacts completely with LaF3 to form a LaOF compound in the solid state below the melting temperature of the sample. LaOF is not completely dissolved in the fluoride melt and solid LaOF is observed in the (19)F spectra for Li2O concentrations above 10 mol%. We discuss the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 84 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…They proved that dissolution of Nd 2 O 3 in NdF 3 -LiF is attributed to a reaction of Nd 2 O 3 + NdF 3 + 3(x À 1)F À ¼ 3NdOF x (xÀ1)À . 28,29 In this study, the precipitated ZrO 2 also reacted with the excessive ZrF 4 and F À at n Zr /n O > 0.5 to form Zr 2 OF x 6Àx complexes as indicated in eqn (3), which obviously increased the solubility of ZrO 2 in the FLiNaK melts. Additionally, the solubility of La 2 O 3 is lower in LiF melts 27 than that in LaF 3 -LiF melts due to the formation of LaO x F y complexes.…”
Section: Chemical Interactions Between Zirconium and Free Oxide In Momentioning
confidence: 73%
See 1 more Smart Citation
“…They proved that dissolution of Nd 2 O 3 in NdF 3 -LiF is attributed to a reaction of Nd 2 O 3 + NdF 3 + 3(x À 1)F À ¼ 3NdOF x (xÀ1)À . 28,29 In this study, the precipitated ZrO 2 also reacted with the excessive ZrF 4 and F À at n Zr /n O > 0.5 to form Zr 2 OF x 6Àx complexes as indicated in eqn (3), which obviously increased the solubility of ZrO 2 in the FLiNaK melts. Additionally, the solubility of La 2 O 3 is lower in LiF melts 27 than that in LaF 3 -LiF melts due to the formation of LaO x F y complexes.…”
Section: Chemical Interactions Between Zirconium and Free Oxide In Momentioning
confidence: 73%
“…The oxyuorides in molten uorides have already been addressed in the eld of rare earth [27][28][29][30][31][32][33][34] and aluminum production. 35, 36 Stefanidaki 32 found that the solubility of Nd 2 O 3 at 900 C increased to 0.15, 0.22 and 0.38 mol% when NdF 3 in LiF melt was increased to 15, 23 and 30 mol%, respectively.…”
Section: Chemical Interactions Between Zirconium and Free Oxide In Momentioning
confidence: 99%
“…On the one hand, when the added RE 2 O 3 was lower than solubility, all the added RE 2 O 3 chemically reacted with melts to form REOF and then completely dissolved in the melts. On the other hand, when the added RE 2 O 3 was higher than solubility, to add RE 2 O 3 continuously not only didn't increase the concentration of RE ions but also reduce the content of REF 3 by form of REOF sunk to the bottom according to references [11,22,13]. By linear fitting the curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the solubility of REO in fluoride melts was widely researched [10][11][12][13][14][15][16][17][18][19][20][21]. It was found that the solubility was relatively low and the melts with high temperature and strong corrosiveness so that there were difficulties for accurate measuring the concentration of REO in fluoride melts.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] For the related research on lanthanide oxyfluoride, in addition to lanthanum oxyfluoride, there were only relevant reports on neodymium and lutetium oxyfluorides using Raman spectroscopy. [19,20] Combined with these above studies, the structural information of fluorides in the melt has been obtained by experimental and theoretical methods, but these studies were mainly focused on lanthanum fluoride, and so far, to the best of our knowledge, no study has been devoted to investigate the cerium fluoride and oxyfluoride species in molten salt. Raman spectroscopy has been widely recognized as one of the key methods to study the microstructure of molten salt with the aid of theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%